Strengthening of masonry walls using hybrid-fiber engineered cementitious composite - Lin, V. W. J. (2015)
In this article, the experimental results of hybrid-fiber engineered cementitious composite (HFECC)-strengthened masonry walls subjected to quasi-static out-of-plane loadings are reported. The aim is to assess the extent to which HFECC-strengthening systems can improve the out-of-plane resistance of unreinforced masonry walls. A total of 12 masonry panels were fabricated and tested in the laboratory under both patch load and uniformly distributed load. Test results showed significant improvement of HFECC-strengthened masonry wall’s performance against out-of-plane loadings. To provide design aid for such HFECC-strengthened masonry walls, simplified theoretical models were also developed to predict its out-of-plane ultimate load-carrying capacities based on the observed failure mechanisms. The theoretically predicted values compared favorably with experimental data.